Protein O-mannosylation is crucial for cell wall integrity, septation and viability in fission yeast - Willer, Tobias; Strahl, Sabine (Molecular microbiology, 2005)
Protein O-mannosyltransferases (PMTs) initiate the assembly of O-mannosyl glycans, which are of fundamental importance in eukaryotes. The PMT family, which is classified into PMT1, PMT2 and PMT4 subfamilies, is evolutionarily conserved. Despite the fact that PMTs are crucial for viability of baker's yeast as well as of mouse, recent studies suggested that there are significant differences in the organization and properties of the O-mannosylation machinery between yeasts and mammals. In this study we identified and characterized the PMT family of the archaeascomycete Schizosaccharomyces pombe. Unlike Saccharomyces cerevisiae where the PMT family is highly redundant, in S. pombe only one member of each PMT subfamily is present, namely, oma1+ (protein O-mannosyltransferase), oma2+ and oma4+. They all act as protein O-mannosyltransferases in vivo. oma1+ and oma2+ form heteromeric protein complexes and recognize different protein substrates compared to oma4+, suggesting that similar principles underlie mannosyltransfer reaction in S. pombe and budding yeast. Deletion of oma2+, as well as simultaneous deletion of oma1+ and oma4+ is lethal. Characterization of the viable S. pombe oma1Δ and oma4Δ single mutants showed that a lack of O-mannosylation results in abnormal cell wall and septum formation, thereby severely affecting cell morphology and cell-cell separation.